2020
DOI: 10.1101/2020.08.21.262329
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impaired cytotoxic CD8+ T cell response in elderly COVID-19 patients

Abstract: SARS-CoV-2 infection induces a T cell response that most likely contributes to virus control in COVID-19 patients, but may also induce immunopathology. Until now, the cytotoxic T cell response has not been very well characterized in COVID-19 patients.Here, we analyzed the differentiation and cytotoxic profile of T cells in 30 cases of mild COVID-19 during acute infection. SARS-CoV-2 infection induced a cytotoxic response of CD8+ T cells, but not CD4+ T cells, characterized by the simultaneous production of gra… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
31
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 41 publications
4
31
0
Order By: Relevance
“…We found no differences between elderly patients (defined as ≥80 years) and patients <80 years old concerning the immunological parameters analyzed, as reported recently in the literature 18,19 . These results could derive from the small number of patients analyzed and/or from the group of patients enrolled in the study with severe COVID‐19.…”
Section: Discussionsupporting
confidence: 80%
“…We found no differences between elderly patients (defined as ≥80 years) and patients <80 years old concerning the immunological parameters analyzed, as reported recently in the literature 18,19 . These results could derive from the small number of patients analyzed and/or from the group of patients enrolled in the study with severe COVID‐19.…”
Section: Discussionsupporting
confidence: 80%
“…Functional analysis further revealed that upregulation of degranulation capacity and cytotoxic molecules in CD4+ and CD8+ T cells in PPSs compared with NPSs. Our findings are in line with published papers(42)(43)(44).SARS-CoV-2 infection may induce a cytotoxic response, characterized by simultaneous production of GZMB and perforin in T cells, NK cells and γδ T cells inPPSs. Excessive activation of cytotoxic T, NK and γδ T cells is not protective but rather drives pulmonary damage after SARS-CoV-2 infection.Emerging evidence suggests that COVID-19 survivors have impaired lung function, with the development of pulmonary fibrosis(2,14).…”
supporting
confidence: 92%
“…In contrast to our results, in young patients, granzyme A or B and perforin levels were increased in mild and moderate cases. Conversely, in elderly COVID-19 patients, there was a reduced expression of granzyme A and perforin [61]. Another study suggested that decreased perforin and granzyme A levels in CD4 þ T cells, CD8 þ T cell and NK cells is associated with severely afflicted COVID-19 patients [62].…”
Section: Discussionmentioning
confidence: 99%